Роль комплексного підходу до інтеграції різночасової архітектури в історичне міське середовище - Запунна, Є. О. (Видавництво Львівської політехніки, 2016)
Розглянуто методологічні підходи до трансформації історичного урбанізованого середовища з метою узагальнення теоретичних знань та практичного досвіду про гармонійний містобудівний простір поселень з давньою історією. Здійснено систематизацію наукових джерел за принципами усебічного висвітлення способів співіснування різночасових компонентів міського оточення; проведено огляд факторів, які впливають на гармонізацію урбанізованого середовища; проаналізовано наукові праці, у яких розглядалися питання інтеграції історичної архітектури у сучасну тканину міста та вперше узагальнено практичний досвід зарубіжних країн щодо шляхів адаптації об’єктів архітектурних пам’яток до сучасних соціокультурних потреб. We have considered the methodological approaches to the transformation of the historic urban environment in order to generalize the theoretical knowledge and practical experience of harmonious urban space settlements with a long history. The cultural heritage of past eras creates a kind of information broadcasting channel influencing people that is enhanced or diminished depending on a number of qualitative characteristics of urban space. Thus, the problem of urban transformation is to emphasize the identity of the urban landscape while maintaining stylistic and proportional balance etc. The main difficulty is that there is no a single recipe as to how to make the historic urban landscape harmonious, functional and aesthetic at the same time to give a positive psychoemotional impression on people. The article describes the systematization of scientific sources on the principles of a comprehensive coverage of the ways of coexistence of different time components in urban environment; the list of factors affecting the harmonization of urban environment; the analysis of scientific works on the integration of historic architecture in a modern city; originally generalized experience of foreign countries in adapting architectural heritage to modern social and cultural needs. We have works dealing with theoretical problems of urban aesthetics and ways to improve it; carried out development of methodological foundations and practical approaches to solving problems of urban environment transformation, monuments reconstruction in the historic urban space; the works in which the understanding of the cultural heritage protection was expanded. Another focus of the study was to analyze the research papers on the issue of adapting historical heritage to modern conditions and coexistence of different time components in historic areas of cities, preservation of religious buildings and structures as well as the means of providing them with a “new” life. We have shown a number of successful, in our opinion, projects for incorporation of historical heritage centres in contemporary urban space: Church of St. Francesc convent in Santpedor, Art Museum in Malmo, Center of community life in Gonzaga, Mill City Museum, “St. Paraskeva” church in Nessebar etc. As a result of theoretical research analysis and practical experience on how to integrate different time architecture into modern urban space, the author found that approaches to integration of different time architecture in the urban environment greatly depend on the degree of preservation of historical heritage centres. Therefore, the comprehensive approach made it possible to specify the ways to revivify the valuable historical heritage centres in the urban environment, which differ both in the degree of modifications to be made and in their perceptual characteristics. The analysis of the aforementioned theoretical research and practical experience on how to integrate the different time architecture into the modern urban space also allowed to formulate the following: 1) different as to preservation level sites shall be integrated into urban environment in different ways: restoration with possible change of functional profile shall be used for maximum preservation; reconstruction with or without any change in functional profile as well as modernization with new construction elements shall be used for half-ruined sites; conservation of the existing conditions and/or arrangement of new social and cultural space integrating the remains of the sites into the newly created architectural form shall be used for ruins; 2) the domestic architectural theory and practice need new modern methods relating to resolving the issues of coexistence of different time architectural developments and transformation of the historic environment depending on its individual characteristics.
Role of comprehensive approach to different time architecture into the historical urban environment
Keywords: історичне міське середовище; інтеграція; різночасова архітектура; реконструкція; адаптація; historical urban environment; integration; different time architecture; reconstruction; adaptation; 711.4:72.01:719 (045)